A Novel Functional Assay of Protein C in Human Plasma and fts Comparison with Amidolytic and Anticoagulant Assays - Guglielmone, H A; Vides, M A (Thrombosis and Haemostasis, 1992)
A simple and fast method for the quantitative determination of protein C activity in plasma is here described. The first step consists in the conversion of protein C in the test sample into activated protein C by means of an activator isolated from Southern Copperhead venom. Subsequently, the degradation of factor Va, in presence of protein C-deficient plasma, is measured by the prolongation of the prothrombin time which is proportional to the amount of protein C in the sample. The dose-response curve showed a linear relationship from 6 to 150% protein C activity and the inter- and intra-assay reproducibility was 3.5% and 5.6% respectively. In normal subjects, a mean of protein C level of 98 ± 15% of normal pooled plasma was found. Comparison with the anticoagulant assay in samples of patients with oral anticoagulant, liver cirrhosis, disseminated intravascular coagulation and severe preeclampsia revealed an excellent correlation (r = 0.94, p <0.001). Also, a similar correlation (r = 0.93, p <0.001) existed between amidolytic assay and the method here proposed for all the samples studied without including the oral anticoagulant group. These results allowed us to infer that this method evaluates the ability of protein C to interact with protein S, phospholipids, calcium ions and factor Va.